The role of rational decisions in technical inefficiency analysis of Spanish pig farms: The influence of water use management - Ait Sidhoum, Amer; Vrachioli, Maria; Guesmi, Bouali; Gil, J. Maria (Elsevier BV, 2023)
There has been limited research on the degree to which rational inefficiency arises when environmental factors are considered. Thus, our goal is to contribute to the literature by applying the concept of rational inefficiency to pig farming and investigating the relationship between water use and farm technical efficiency levels. This research aims to provide a better understanding of the complex interactions between pig farming production, the natural environment, and economic performance. The stochastic frontier analysis is applied to a cross-section dataset of 523 Catalan farms specialized in pig production in 2018. The main findings of this study are as follows: First, Catalan pig farming exhibits high levels of technical efficiency with an average score of 0.94, which is consistent with the high intensity and concentration of Spanish pork production. Second, there is no compelling evidence to support the rational inefficiency hypothesis, particularly when comparing the rational efficient and multi-efficient groups.
Keywords: Pig farms; Water use; Environmental concerns; Technical efficiency; Rational inefficiency